Devotion to St. Anne in Texts and Images From Byzantium to the Late European Middle Ages (Springer International Publishing, 2018)
St. Anne was popular with representatives of various segments of society - from monks, nuns, members of the clergy, royal patrons, to church-goers of every rank. This book looks into both the public and private worship of this holy woman and brings to the surface some under-exposed aspects of St. Anne's cult. It does so through the examination of manuscripts, monumental art, relics, sculpture, and texts of various genres. The contributors employ a historical as well as a theological perspective on how the cult of St. Anne (sometimes also with glimpses concerning that of Joachim) established itself; referring to areas in Europe which are not frequently discussed in English-language scholarship. This new contribution to the field of hagiography will be of interest to academics from a variety of research fields, including theologians, Byzantinists, art and church historians, and historians of a larger scope. .